2012
DOI: 10.1021/mp300257x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Administration of the TLR2 Agonist Pam2Cys Provides Rapid Protection against Influenza in Mice

Abstract: The protective role played by the innate immune system during early stages of infection suggests that compounds which stimulate innate responses could be used as antimicrobial or antiviral agents. In this study, we demonstrate that the Toll-like receptor-2 agonist Pam2Cys, when administered intranasally, triggers a cascade of inflammatory and innate immune signals, acting as an immunostimulant by attracting neutrophils and macrophages and inducing secretion of IL-2, IL-6, IL-10, IFN-γ, MCP-1 and TNF-α. These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
126
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(138 citation statements)
references
References 42 publications
12
126
0
Order By: Relevance
“…Specifically, while the innate immune response to B. pertussis is primarily TLR-4-mediated [16], the responses to both M. pneumoniae [17, 18] and C. pneumoniae [19] are driven in large part by TLR-2-mediated pathways. This distinction is important in the context of our analysis, as proper clearance of influenza is also known to rely heavily on TLR-2 recognition [20, 21]. These commonalities in the innate immune recognition of influenza virus and M. and C. pneumoniae could abrogate coinfections with these pathogens and explain the antagonistic effects described here.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, while the innate immune response to B. pertussis is primarily TLR-4-mediated [16], the responses to both M. pneumoniae [17, 18] and C. pneumoniae [19] are driven in large part by TLR-2-mediated pathways. This distinction is important in the context of our analysis, as proper clearance of influenza is also known to rely heavily on TLR-2 recognition [20, 21]. These commonalities in the innate immune recognition of influenza virus and M. and C. pneumoniae could abrogate coinfections with these pathogens and explain the antagonistic effects described here.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite possible that steroid treatment could be effective in humans, but the timing and magnitude of the drug has not yet been optimized. Tan et al [47] have shown Pam2Cys, a TLR-2 agonist, can instigate an inflammatory response even in the absence of an antigen. Mice pre-treated with Pam2Cys were protected from the H1N1 virus for up to seven days post-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these compounds on the dynamic response of the lung immune systems has not been determined. Several experiments have indicated a protective effect of pre-stimulation of TLR pathways before influenza infection in murine models [46][47][48][49]. We tested the three ODE models to determine whether they could replicate these experimental results.…”
Section: Models' Response To Simulated Ifn Pre-stimulationmentioning
confidence: 91%
“…Specific TLR-mediated immunostimulation was also demonstrated in previous studies to increase the innate immune response and resistance to lethal influenza virus monoinfection in vivo. However, treatment was initiated prior to infection (42,43) or no later than 24 h after infection (44), although a highly increased susceptibility to secondary pneumococcal invasion associated with impaired bacterial clearance (19) and high mortality rates (45) was detected between days 5 and 7 after influenza virus infection. Notably, in the present study, pulmonary TLR-mediated immunostimulation with MALP-2 effectively increased the level of proinflammatory IL-1␤ and subsequent immigration of leukocytes, particularly neutrophils and macrophages, into murine airways even 6 days after IAV infection, despite an ongoing antiviral host defense.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, pulmonary immune stimulation with MALP-2 5 days after IAV infection (24 h before pneumococcal challenge) also resulted in decreased lung bacterial loads 24 h after bacterial infection. Moreover, specific TLR-mediated immunostimulation prior to or shortly after experimental influenza virus monoinfection has been shown to reduce the viral titer (43,44). However, MALP-2 treatment performed on day 5 after IAV infection had no effect on viral load or viral distribution in the murine lung tissue.…”
Section: Discussionmentioning
confidence: 99%